THE ROLE OF RELIGION IN THE HOUSEHOLD IN STRENGTHENING STUDENTS' MOTIVATION FOR LEARNING ISLAMIC RELIGIOUS EDUCATION - Fadhilla, Nada; Fahrurrozi, Muhammad (Prodi PAI STIT Sunan Giri Bima, 2023)
The role of religion at home is very important in increasing learning motivation. Because parents are the first education for children. This study discusses the role of religion at home in strengthening the learning motivation of religious education students. The aim of this study was to determine the role of religion and parents in increasing the learning motivation of Islamic religious education students. The research method used is qualitative research which describes the location agreement in a narrative way and research data is obtained through observation, interviews, and documentation. The data from the research results were analyzed and then concluded and narrated. The results of the study revealed that the role of religion at home in improving the learning achievement of Islamic education students uses forms and models, namely: Education and exemplary, Education with habituation, education with good advice, education with giving attention and supervision, education with punishment. The research findings suggest that the role of religion and parents is able to carry out and generate motivation to study Islamic religious education students.